The leap to leader : how ambitious managers make the jump to leadership - Bryant, Adam (Ascent Audio, 2023)
The chasm separating managers from leaders is widening, because the responsibilities of leaders, and the skills required to be effective in the role, are growing in number and complexity. But you are ambitious. You want to cross that chasm. And your organization needs you to cross it in order to build its bench of leaders who will lead with empathy and humanity and ground the organization's strategies in a broader sense of mission and purpose. The Leap to Leader is your trusted playbook for making the biggest jump of your career. Foregrounded by compelling stories of those who've made the leap, this book describes what it takes to become a confident leader. Successful CEOs and other C-suite leaders share their strategies and tactics for building a loyal following, winning promotions without asking for them, developing a legacy by helping others make the leap to leader, and much more. Written by Adam Bryant, creator and former author of the iconic Corner Office column in the New York Times, now managing director at The ExCo Group, The Leap to Leader draws on his work with hundreds of fast-rising executives and shares the leadership-development frameworks, tools, and approaches that have helped these leaders succeed.